Tinjauan Hukum Islam Terhadap Praktik Penggunaan Label Produk Makanan yang Menggunakan Kata Menyeramkan di Pekalongan - Mayangsari, Putri Ayu; Khasanah, Karimatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Lately, in Indonesia, food and beverage products are rife that use scary names. In Pekalongan itself there are also restaurants or home products that use scary names, including: Mie Setan Geprek; Satan's Botok and Devil's Claw Mbak Ilma. Therefore, it is important to know how to use these names in the perspective of Islamic law. This research is an empirical legal research using a sociology of law approach. The results of this study indicate that in positive law there are no rules that prohibit the use of scary words for food labels, so it is okay to use scary words on food product labels. However, according to Islamic business ethics and MUI Fatwa Number 4 of 2003 concerning Standardization of Halal Fatwa, food product labels should not use the word scary because it is not in accordance with Islamic law. The importance of food products using names that are in accordance with Islamic ethics is also in line with the enactment of Law Number 33 of 2014 concerning Halal Product Guarantee where food products must have a halal certificate, while one of the requirements to be certified halal is to meet the criteria set by MUI considering BPJH cooperate with MUI in issuing decisions to determine halal products.